Enhancing patient experience through personalization of health services. Issue 5 (September 2015) - Snowdon, Anne W.; Alessi, Charles; Bassi, Harpreet; DeForge, Ryan T.; Schnarr, Karin
Patient engagement is a challenge many leaders are facing, as consumer expectations of health services demand a more personalized approach to care. This article examines consumer trends that are influencing patient engagement and empowerment relative to the use of digital technologies. Informed by consumer and population health trends that can personalize health services, three strategies leaders can engage to strengthen patient experience include placing greater focus on personal health and wellness, shifting towards personalized rather than standardized healthcare, and facilitating the democratization of healthcare information.